Chirurgická léčba akromioklavikulární luxace: Tahová cerkláž versus hákovitá dlaha - Tuček, M; Chochola, A; Vaněček, V; Bušková, K (Rozhledy v chirurgii, 2015)
INTRODUCTION: The aim of the prospective randomized study was to compare tension wire cerclage and hook plate in the treatment of AC dislocation, primarily from the viewpoint of functional and radiological results. METHOD: The cohort comprised 80 patients with acute acromioclavicular (AC) dislocation of types 3, 4 and 5 of Rockwood classification. The diagnosis was based on the clinical (disfiguration and instability) and radiographic examination (AP and stress radiograph). Forty patients were treated with tension band wiring (TBW) and another 40 with a hook plate (HP). Evaluation was performed during one year after the surgery based on radiographs and the Constant score. RESULTS: The mean Constant score 3 months after the surgery was 84 points for TBW and 88 points for HP. One year after the surgery, the result was the same in both groups: 93 points. In HP group the score increased from 56 to 78 points between 2 and 4 weeks from the surgery. In 71 cases the postoperative position of the AC joint and implant was assessed as correct. Malposition of Kirschner wires was recorded in 6 cases and horizontal widening of the AC joint in 3 cases. Redislocation of up to 50100% of the width of acromion was shown by radiograph in 4 TBW patients (10%) and in 5 HP patients (13%). A visible osteolysis of the distal surface of acromion was found in 83% of patients with HP. Complications were recorded in 30% of TBW patients and in 5% of HP patients. CONCLUSION: Based on radiological and clinical results assessed 3 months and 1 year after the surger, the hook plate and tension band wiring are comparable treatment methods for AC dislocation. The hook plate is associated with a lower complication rate and allows earlier full weight bearing and mobility than tension wire cerclage. In TBW we recommend to remove the implant after 8 weeks; 6 weeks are in our view too short a period for the healing of soft tissues. In HP it is suitable to remove the hardware by 3 months due to potential subacromial irritation and pressure-induced osteolysis.
Keywords: senioři; akromioklavikulární kloub; výsledek terapie; dislokace kloubu; Middle Aged; mužské pohlaví; Fracture Fixation, Internal; Prospective Studies; Adult; mladý dospělý; Joint Dislocations; kostní destičky; Young Adult; ženské pohlaví; Humans; prospektivní studie; Acromioclavicular Joint; poranění hrudníku; vnitřní fixace fraktury; lidé středního věku; Thoracic Injuries; Bone Plates; kostní dráty; dospělí; Bone Wires; Female; Aged; Treatment Outcome; lidé; Male